Synthesis of (+)‐Schisanwilsonene A by Tandem Gold‐Catalyzed Cyclization/1, 5‐Migration/Cyclopropanation1. Issue 25 (10th May 2013) - Gaydou, Morgane; Miller, Ricarda E.; Delpont, Nicolas; Ceccon, Julien; Echavarren, Antonio M.
<x xml:space="preserve">Abstract</x> Going (anti)viral: The first total synthesis of the antiviral (+)‐schisanwilsonene A has been completed using a fully stereoselective tandem cyclization/1, 5‐migration/intermolecular cyclopropanation. The key reaction sequence is catalyzed by gold.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>